Audit and education: Role in safe transfusion practice - Gopal Kumar Patidar; Daljit Kaur (Asian Journal of Transfusion Science, 2018)
Background: Auditing and education are the tools for improvement in the transfusion practices. Clinicians are not providing patient's demographic data and medical history to the blood bank that required transfusion. This missing information in blood request forms can lead to transfusion reactions to the patient. So we planned to analyse the blood request forms received at our blood bank and the impact of educational program for the clinicians. Methods: A total of 6894 blood request forms were received from the month of July 2014 to December 2014 at a blood bank in Amritsar, India. We evaluated for completeness of the blood request form in parameter columns like second identification (CR No. or Father/Husband Name), diagnosis, pre transfusion hematological parameters, quality and quantity of blood component required, history of previous transfusion and adverse transfusion reaction, urgency of transfusion, medical officer name and signature, phlebotomist name and signature etc. A series of CMEs on “Safe Transfusion Practices” were organized for clinicians and hospital staff from 1st August 2014 and improvement in clinicians' behavior was analysed. Results: A total of 60.83% requests were not filled completely during the study period. Of these 91.42% were in the month of July, which decreased to 48.76% in the month of December 2014 with a total improvement of 42.66%. Incomplete second identification (91.03%) and history of previous transfusion and adverse transfusion reactions (80.21%) were the commonest incomplete fields in the month of July 2014. In the month of December 2014, an improvement in incomplete second identification was observed (12.8%) however phlebotomist signature was still a major incomplete field (45.19%). A statistically significant (p value = 0.004, paired 't' test) improvement in completeness of forms was observed. Summary: Results of medical audit and using those as a basis for developing a highly targeted educational program, can improve the clinicians' approch towards transfusion practices.